Eficiência do poder judiciário à luz dos novos mecanismos da conciliação e da mediação - Freitas, Sandra Neder Thomé de (2019)
The globalization and the fast changes concerning the application of what is right and what is fair put society on a pressure situation that ends up increasing exponentially the litigious nature of many situations that, in Brazil, flood the Judiciary Power with processes that take years to be solved. In this scenario rises the need of finding mechanisms that contribute to the resolution of these conflicts so that the justice appliance reaches the jurisdiction in a fast, effective and efficient way. It’s in this scenario that the Conciliation and the Mediation institutes should be analyzed, once they arise as alternatives mechanisms capable not only of settling such conflicts, but, overall, as a way of preventing litigation, avoiding, most of times, that the toils come to the door of the Judiciary Power. In that sense, the work concludes that such mechanisms can contribute significantly to the decrease of the numbers of demands on the Judiciary and, therefore, to reach its efficiency and effectiveness. The methods utilized were the hypothetical-deductive, to the comprehension of the meaning and concepts here applied and the inductive, when analyzed the numbers of the Judiciary Power to draw general conclusions about the efficiency, effectiveness and effectiveness of the Conciliation and Mediation institutes.